A better understanding of good ethical practices in contractor companies - Hashim, Norfashiha; Adnan, Hamimah; Mohd Yusuwan, Norazian (2011)
Ethics affects corporate credibility and economic sustainability as well as personal security. There is a growing consensus within and outside the construction industry that corruption and other unethical practices are endemic in the construction industry. In achieving professional excellence, it is important that construction practitioners not only concentrate on technological advances but also put ethics in action. It is important to reflect on ethical issues and unethical practices prevalent in the construction industry in order to overcome the problems prevailing in the industry. This research is alms to identify the perceptions of contractors towards the ethical practices in construction industry and to make recommendations of good ethical practice among contractors in Malaysia. This research is mainly a quantitative research which involved questionnaires survey to Grade G7 Contractor registered under Construction Industry Development Board, Malaysia in Klang Valley area. The survey found that level of unethical behaviors in construction industry perceived by contractors are generally serious and the industry is very susceptible with the unethical conduct. These are cover pricing, bid cutting, poor documentation, late payments and short payment, subcontractor (no safety ethics), unfair treatment of contractors in tender/final account negotiations, competitors overstating their capacity and qualifications to secure work, competitors falsifications of experience, capabilities and qualifications and bureaucratic.